Increasing Population Knowledge: The Comparation of Problem Solving Learning Methods with Conventional Methods - Nurdin Nurdin (Jurnal Pendidikan dan Pengajaran, 2021)
This study aims to analyze the effect of teaching methods using problem solving and conventional on population knowledge. The research was conducted experimentally with a 2x2 factorial design on 80 students consisting of 40 students having a high attitude, and 40 students having a low attitude at the Junior High School 2 Tambun Selatan-Bekasi. Data collection regarding population knowledge was carried out using an objective test instrument with the answer choices True (B) with a score of 1 and False (S) with a score of 0. The data were analyzed by means of two-way analysis of variance, and the Tukey test. Research results There are differences in population knowledge learning outcomes between students who are given problem solving teaching methods and students who are given conventional teaching methods; There is an interaction between teaching methods and students' attitudes towards population knowledge; Study groups that have high and low attitudes have higher population knowledge learning outcomes when given problem solving teaching methods compared to students who are given conventional teaching methods. The implication is that teachers in teaching must always build a high attitude in the classroom so that positive interactions occur in the teaching and learning process by using various learning methods.